IMPACT DEGREE OF THE TOTAL QUALITY MANAGEMENT ON THE PUBLIC SCHOOLS EFFECTIVENESS IN THE GOVERNORATE OF JARASH AS VIEWED BY THE EDUCATIONAL SUPERVISORS - Jaradat, Mohammed Hasan (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿This study aimed to identify the impact degree of the applying the total quality criteria on the public schools effectiveness in the Governorate of Jarash as viewed by the educational supervisors. In order to realize the objective of this study, a 5-item questionnaire was constructed distributed over four areas (School Administration, Teaching and Learning, Links with the Community and School Activities). The validity and reliability of the instrument were verified, and the study population consisted of all the educational supervisors (n=35) in the Directorate of Education of the Governorate of Jarash-Jordan, during the 2012/2013 academic year. They were sent 35 questionnaires, out of which 30 were returned and were suitable for the study. Following the information and data collection, they were analyzed for the purposes of the study. The results showed that the impact degree of applying total quality criteria on the public schools effectiveness in the Governorate of Jarash, as viewed by the educational supervisors, was high for all the areas. However, the school administration area ranked first with a high degree of impact on the school effectiveness. On the other hand, the school activities area came last and still with a high degree of effectiveness. The study recommended generalizing the experience of applying the total quality criteria on all the Jordanian schools due to their impact in increasing the school effectiveness.